2019
DOI: 10.7567/1347-4065/ab460b
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the current injection issue in the 310 nm band AlGaN UVB light-emitting diode

Abstract: AlGaN-based ultraviolet-B (UVB) LEDs at 310 nm emissions are expected to offer safe and smart size UVB-light sources compared to the toxic mercury UV-lamp. Previously, the issue of nonlinearity in the emitted light output power (L) as well as in the external quantum efficiency (EQE) of 310 nm band UVB LEDs were observed. First, the influence of both the number of n-AlGaN buffer layers (BLs) and the type of p-electrodes on the recovery of linear behavior in the L and EQE were investigated. It was found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(79 citation statements)
references
References 34 publications
1
78
0
Order By: Relevance
“…Previously, the influence of ∼ 50% relaxed n-type AlGaN ESL in 310 nm-band MQWs on PL intensity was reported 8 . However, the influence of ∼ 49% relaxed n-type AlGaN ESL in 304 nm-band MQWs on PL intensity is rarely reported in our previous work 8 , 25 , 26 . The relaxation condition in the n-AlGaN ESL underneath the MQWs, strongly influences the piezoelectricity, extended defects, point defects, Al-alloy fluctuation and nonradiative recombination centers (NRCs) in the MQWs, which ultimately degrade the IQE 4 , 8 , 16 , 26 , 37 , 38 .…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Previously, the influence of ∼ 50% relaxed n-type AlGaN ESL in 310 nm-band MQWs on PL intensity was reported 8 . However, the influence of ∼ 49% relaxed n-type AlGaN ESL in 304 nm-band MQWs on PL intensity is rarely reported in our previous work 8 , 25 , 26 . The relaxation condition in the n-AlGaN ESL underneath the MQWs, strongly influences the piezoelectricity, extended defects, point defects, Al-alloy fluctuation and nonradiative recombination centers (NRCs) in the MQWs, which ultimately degrade the IQE 4 , 8 , 16 , 26 , 37 , 38 .…”
Section: Resultsmentioning
confidence: 75%
“… Sources References UVB LED structure Max. output power EQE Wavelength CNRS Brault et al 17 Sapphire/AlN/AlGaN-QD 0.25 mw @ 100 mA 0.15% @ 20 mA 305–320 nm Kansas State University Kim et al 18 Sapphire/AlN/AlGaN-QW/p-AlGaN (in-dot quick test) 1.8 mW @ 350 mA Un-known 290 nm 305 nm TU Berlin/FBH Enslin et al 19 Rass et al 20 Guttmann et al 21 Susilo et al 22 Sapphire/AlN/AlGaN-QW/p-GaN (in-dot quick test) 9 mW @ 20 mA 18 mW @ 500 mA 1–2% @ 20 mA 302 nm 310 nm Riken Khan et al 24 Khan et al 23 Khan et al 23 Khan et al 25 Khan et al 26 Khan et al 8 Khan et al 8 Sapphire/AlN/AlGaN-QW/p-AlGaN (in-dot quick test) 12.5 mW @ 130 mA 7.1 mW @ 180 mA 13 mW @ 130 mA 12 mW @ 140 mA 17 mW @ 150 mA 32 mW @ 170 mA 30 mW @ 220 mA 3.3% @ 20 mA 0.5% @ 20 mA 4.4% @ 30 mA 2.4% @ 20 mA 5.6% @ 30 mA 6.5% @ 30 mA 4.7% @ 30 mA 294 nm 310 nm 295 nm 310 nm 295 nm 300 nm 310 nm This work 40 mW @ 170 mA 9.6% @ 10 mA 304 nm …”
Section: Introductionmentioning
confidence: 99%
“…Early report mainly focused on band diagram engineering by modifying the epitaxial structure of p-EBL [14]- [16]. Recently, Khan et al demonstrated that reducing the thickness of quantum barrier of MQWs is also favorable for hole transport and carrier distribution in MQWs [17]. Another viable scheme to enhance the hole injection efficiency is to utilize polarization doping.…”
Section: Introductionmentioning
confidence: 99%
“…And also make the series resistance larger, resulting in bias loss. [20,21] In addition, because of the effects of light absorption and the series resistance, the thickness of the p-GaN contact layer cannot be greater than 40 nm. Therefore, the mismatch in the degrees of electron/hole injection in the active layer of the quantum well will lead to a lack of quasi-charge neutrality.…”
Section: Introductionmentioning
confidence: 99%